La influencia de los programas radiales musicales locales en la promoción de los músicos afiliados a la “Asociación de Artistas Profesionales de Loja” (ASAPLO), Ecuador, durante el año 2017. Propuesta alternativa. - Redrovan Criollo, Greeys Andrea (2019)
Loja, known as the city "Cuna de artistas" is the owner of many talents in different artistic fields, particularly in music, groups, bands, duets, trios, soloists, performers and composers in different genres and rhythms stand out. covered by the changes in the Organic Communication Law in force since June 25, 2013, which in sections VI and VII, which corresponds to the national production, in Art. 103, establishes that "the cases of the stations of sound broadcasting that broadcasts musical programs, the music produced, composed or performed in Ecuador, represent at least 50% of the musical content broadcasted in all its schedules, with the payment of the author's rights are established in the law ". The present investigation has like general objective to analyze how the musical radial programs influence in the promotion of the musicians affiliated to the "Association of Professional Artists of Loja" (ASAPLO). To select the information, the ethnographic method was used, as well as the participatory action method, applying observation cards, surveys and interviews, techniques that allowed a key approach with the social actors, a clearer definition of the topic to be investigated. The contracts with a business relationship with the offer of services and local radio media, in accordance with the conditions of the promotion of advertising and artistic promotion. With this we do not mean that the relationship between musicians and media mar mala; however, the lack of promotion and communication strategies that are not allowed to bring out our lively musical art in a more effective way. The purpose of this work is to contribute with the artistic community of ASAPLO with ideas that allow access to the appropriate public of their media.